LA PRODUCCIÓN DE LA IMPRENTA REAL A FINALES DEL SIGLO XVIII: HACIA LA CONSTRUCCIÓN DE UN CATÁLOGO - Alba de la Cruz Redondo (Cuadernos de Ilustración y Romanticismo)
In the 18th century there was a series of economic, sociocultural and propaganda factors that transformed the print into a useful tool for the power. This lead to creating a specific printing house belonging to the monarchy in a similar fashion to other European countries. Although the Imprenta Real —the Spanish Royal Print— was devoted to produce official texts at the beginning, the number of publications increased till other printers considered there was an intromission in their business because of the abuse of power. The aim of this article is to describe the bibliographic collections produced by the Imprenta Real Print through the preserved catalogues.